Constitutional touchstones: Peace processes, federalism, and constitution-making in Myanmar. (28th January 2021) - Crouch, Melissa
Abstract: A constitutional touchstone is a document that articulates alternative constitutional proposals and is a symbolic resource in discussions of constitutional reform. Such documents keep alive opposition constitutional aspirations. Constitutional touchstones enhance understanding of the influence of constitutional history on contemporary efforts at peace and constitutional reform. Through successive constitutional reform processes, constitutional touchstones articulate future visions for reform and emerge as a reference point for political dialogue on peace and constitutional change. Through the case of Myanmar, I consider the influence of constitutional touchstones on contemporary constitution-making and trace demands for federalism through four stages of peace processes in Myanmar. Constitutional touchstones are important considerations that shape the terms of a peace process and condition, though do not determine the limits of constitutional reform. Presenting an alternative view to the idea that constitution-makers and peace negotiators in a globalized age are primarily focused on best practice or the most suitable comparative models, I draw attention to the ongoing salience and social life of past constitutional debates in contemporary peace processes.